The prevalence and related factors of familial hypercholesterolemia in rural population of China using Chinese modified Dutch Lipid Clinic Network definition - Yan Wang; Yuqian Li; Xiaotian Liu; Runqi Tu; Haiqing Zhang; Xinling Qian; Jingjing Jiang; Dou Qiao; Xue Liu; Zhicheng Luo; Xiaokang Dong; Chongjian Wang (BMC, 2019)
Abstract Background Familial hypercholesterolemia (FH) is a common monogenic disease, while studies about the epidemiology for the general population in China was scarce. Aim of the study was to estimate the prevalence of FH and explore related factors by the Chinese modified Dutch Lipid Clinic Network (DLCN) definition. Methods A total of 39,205 participants (15,463 males and 23,742 females) aged 18-79 years old were enrolled from the Henan Rural Cohort Study. FH was defined by the Chinese modified DLCN definition, and score > 5 was classified as FH. Logistic regression analysis was used to calculate the odds ratio and 95% confidence interval. Results Crude prevalence of probable/definite FH was 0.35% (0.29-0.41%), estimated by the Chinese modified DLCN definition. Prevalence in female was 0.38%, and in male, it was 0.32%. Age-standardized prevalence in female increased significantly around the age of 50 years. Moreover, there were no FH patients getting low-density lipoprotein cholesterol controlled to the recommended level. Multivariate logistic regression identified that older, overweight/obesity were positively associated with FH. Conclusions The current study indicated that FH was not rare in rural area of China (1 in 286). Effective early detection and timely control of FH must be strengthened to reduce disease burden.